PERSEPSI MASYARAKAT DESA RASAU JAYA UMUM BERDASARKAN INDIKATOR PENGAMATAN TERHADAP KEGIATAN BRIGDALKARHUTMANGGALA AGNI DAOPS PONTIANAK - Haliantika, Pela; Zainal, Sofyan; Dirhamsyah, M. (Universitas Tanjungpura, 2015)
In the forest and land use are many factors that cause the destruction of forests and the land, one of which is the activity of the people who frequent cultivation by burning one of which occurred in the village of Rasau Jaya Umum.. The method used was a survey method with interview-assisted questionnaire. Determination of the number of respondents using Slovin formula and its determination by purposive sampling. Data analysis using Chi Square formula. Public perception Rasau Jaya Umum Village Observations Based Indicators of Activity Against Brigdalkarhut Manggala Agni Daops Pontianak tend to differ. Analysis of the data showed 64.20% of all respondents are neutral, it is because there are some people Rasau Jaya Umum Village felt that the activities carried out by Manggala Agni Brigdalkarhut Daops Pontianak positive impact and people who are active in the burning of land, they have to have eyes other income not related to combustion, burning only do they do at a time when free to grow crops such as corn, pineapple and others,. Independent variables that have a real relationship / significant to the public perception Rasau Jaya Umum Village Observations of activity indicator Brigdalkarhut Manggala Agni Daops Pontianak is the level of age, level of education, cosmopolitan and while that does not have a real relationship / significant is the level of public knowledge. Keywords: Brigdalkarhut Manggala Agni Daops Pontianak, Perception, Public, Rasau Jaya Umum Village.